Gestión de inventario del Bazar Crisnoelia del Cantón Puebloviejo. - Vera Sellan, Angela Verónica (2022)
Inventory management within businesses is essential for it to provide the organization of the warehouse and for the development of all activities to be correct. In this way, the entity will have enough goods to be able to satisfy the demand for the product, if this management is not carried out correctly, the companies, as a consequence, will assume losses of an inefficient organization, at the same time it would cause losses of clients due to the lack of goods, harming the entity growth. The present study was carried out in the "CRISNOELIA" bazaar business, in the Puebloviejo province of Los Ríos, with the purpose of knowing the factors that are directly affecting inventory management, for which reason an analysis is also carried out on the causes and effects that can be caused in the administrative area of inventories of this business that is dedicated to the commercialization of numerous kinds of product such as: stationery items, for the home, clothing, sandals, jewelry, food, among other things.